(untitled) (Journal of the College of Basic Education, 2022)
Research aims to identify: Skill teaching by teachers of chemistry. Habits of mind produced by teachers of chemistry. The differences in the skillful teaching of chemistry teachers according to the gender variable (male - female). The differences in the habits of the mind produced by chemistry teachers according to the gender variable (male - female). The relationship between the productive habits of the mind and the skillful teaching of chemistry teachers. The extent of the productive habits of mind contributing to the skillful teaching of chemistry teachers. The sample consisted of (400) teachers and chemistry instructors from the three Karkh education directorates (first, second & third), who were chosen using the random stratum method of proportional distribution, by (168) Male & (232) Female. The researcher built the Expertise Teaching scale, which consists of (32) items distributed on (4) sub-skills. And it adopted the Sadawi-Producing Habits of Mind Scale 2016, which consists of (30) behavioral attitudes, distributed into (3) sub habits. The psychometric properties of the two scales were verified. The following statistical methods were used: (Pearson correlation coefficient, AlPha-ronbach coefficient, T-test for one sample, T-test for two independent samples, regression analysis). The following results were reached: Chemistry teachers are characterized by a high degree of teaching aptitude. Chemistry teachers are characterized by a high degree of skills (planning, lesson management, & evaluation). Female teachers excel teachers in the skill of lesson management, while teachers excel in the evaluation skill. Chemistry teachers have a high degree of productive habits of mind. Chemistry teachers excel over female teachers in habits of self-organization and creative thinking, while female teachers excel in habits of critical thinking. There is a positive statistically significant correlation between productive habits of the mind and skillful teaching. The productive habits of the mind (self-organization, critical thinking, & creative thinking) contribute to the skillful teaching of chemistry teachers. The researcher presented a set of recommendations & proposals.